Progress in the Control of Oral Anticoagulation - Loeliger, E. A (Thrombosis and Haemostasis, 1972)
It should be realized that the quality of oral anticoagulation depends on thorough pharmacological knowledge of coumarin congeners, skilled clinical supervision of the patient and well-standardized laboratory control of patients’ blood. Results of the laboratory control should no longer be expressed in terms of conventional prolongation ratios or percentages only. Exact data as to laboratory standardization with reference plasmas and the results of translation into terms of reference thromboplastins have to be given.